Semiconductor-on-insulator materials for nanoelectronics applications - Nazarov, Alexei (Alexei N.) (Engineering Materials, 2011)
"Semiconductor-On-Insulator Materials for NanoElectonics Applications? is devoted to the fast evolving field of modern nanoelectronics, and more particularly to the physics and technology of nanoelectronic devices built on semiconductor-on-insulator (SemOI) systems. The book contains the achievements in this field from leading companies and universities in Europe, USA, Brazil and Russia. It is articulated around four main topics: 1. New semiconductor-on-insulator materials; 2. Physics of modern SemOI devices; 3. Advanced characterization of SemOI devices; 4. Sensors and MEMS on SOI. "Semiconductor-On-Insulator Materials for NanoElectonics Applications? is useful not only to specialists in nano- and microelectronics but also to students and to the wider audience of readers who are interested in new directions in modern electronics and optoelectronics.